PERSAINGAN USAHA ANTARA WARUNG KOPI MODERN DAN WARUNG KOPI TRADISIONAL DI KOTA SAMBAS PERSPEKTIF ETIKA BISNIS SYARIAH - Nursiwan, Titus; Budi Iswanto; Munadi (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The cafe business is currently growing in the community, where the cafe has now transformed into part of a habit or part of an individual group's lifestyle. In the city of Sambas, the development of the cafe business is increasing rapidly. Competition between cafe business people is unavoidable, one form of competition is in the form of products, services, places, prices. This study aims to determine the strategies used by cafe owners in Sambas City. The form of business competition carried out by cafe owners in Sambas City. Application of Islamic business ethics to cafe owners in Sambas City. The type of research used in this thesis is a qualitative descriptive method, the data in this study were obtained from primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. The data analysis technique is using qualitative data analysis. The results of this study indicate that 1) Competition regarding products, cafe owners understand in detail each product they have. Price competition that occurs in cafe business owners in Sambas City is a natural thing to happen. The competition for places among cafe business owners does not occur because basically they say that there is already a set of fortune. The service competition for the cafe business owners in the city of Sambas is mostly good. 2) Competition that occurs in cafe business owners in Sambas City is in accordance with existing Islamic business ethics, this is based on the principles of Islamic business ethics that have been applied.